Survey of pileated gibbon Hylobates pileatus in Thailand: Populations threatened by hunting and habitat degradation - Rungnapa Phoonjampa (2018)
Seventeen protected areas in south-east Thailand were surveyed for the Endangered pileated gibbon Hylobates pileatus during April 2004-March 2005, with the objectives of establishing the species' current distribution, obtaining approximate population estimates for the largest forest areas, and assessing threats to the species' survival. Landsat images and a geographical information system were used to identify the remaining suitable habitat within the species' range. We conducted auditory surveys to census the gibbon populations in the five largest protected areas of Khao Yai, Pang Sida, and Tab Lan National Parks, and Khao Soi Dao and Khao Ang Ru Nai Wildlife Sanctuaries. Small protected areas within the range of the pileated gibbon (five parks and seven sanctuaries) were also evaluated, using questionnaires and interviews with local staff and villagers. Approximately 3,800 km2 of suitable canopy forest with an estimated 3,000 breeding groups, containing c. 12,000 individuals, remain within the four largest areas of forest. Pileated gibbons are also still present in 10 of the smaller protected areas. The largest populations of pileated gibbon in Thailand should be viable over the long-term provided that hunting, habitat degradation and further fragmentation are controlled. Hunting is now the most significant problem, and gibbon densities are well below the carrying capacity of the habitat and declining. As patrolling is not sufficiently effective to control poaching, the cooperation and support of local villagers must be sought in future conservation efforts. © 2008 Fauna & Flora International.